The Role of Accounting Information Systems In Organizational Decision Making: Evidence From Banking Sector In Ghana - Kwadwo Kyeremeh; Bright Bediako Kyeremeh; Matilda Afful Forson (Journal of Accounting and Taxation, 2022)
Accounting information system is very vital in management planning and decision making. The objective of this work was to find out the role of accounting information system in management planning and decision making, with reference to some selected financial institution in Sunyani municipal area. Which includes; how accounting information system helps management in decision making and planning to identify challenges associated with the use of accounting information system in decision making. The method used for the research was based on personal interviews, questionnaires, of the above financial institutions. The research revealed that informed financial decision enhances overall performance of the enterprise. The research showed that, there were some challenges that accounting information system limits the idea of management to only accounting standards, inclusion and omission of accounting information system and is sometimes difficult to understand and this discourage firms and consumers from adopting them for planning and decision making. After the research, it has been recommended that there is the need for banks and other financial institution to educate their staff and consumers about the use of accounting information system and all the pro and cons of each standard and information adopted by the firm. It is inevitable fact that financial institution performs below expectation and some also outside the scope set by accounting standard. The adoption and use of the accounting information system was found to be high but poor in management planning and decision making due to lack of knowledge, consistent changes in accounting standards and also poor timing of information. In conclusion, accounting information system has played an important role in management planning and decision making in the various financial institutions in the world, accounting information system prepares the whole range of different information for different users. The management of different organisation in the world can measure and examine the business quality of the entire institutions on the basic of the accounting and financial information.